(untitled) (Research, Society and Development, 2023)
Ozone is a molecule consisting of three oxygen atoms and was described by Christian Friederick Schonbien in 1840, being used for the first time in dentistry in 1950 by Dr. Edward Fisch. Ozone therapy consists of the ability to dissociate ozone in water and the release of reactive oxygen species (ROS) that will generate oxidative stress triggering biochemical processes such as: antimicrobial, analgesic, anti-inflammatory and healing action, in addition to causing an increase in tissue oxygenation. Research has shown that ozone therapy in dentistry has been shown to be effective in the treatment of oral lesions, in the postoperative period of dental extractions, treatment of carious lesions, treatment of periodontitis and in other areas, restoring oral health and quality of life for the patient. The objective of this work is to present the possibilities of using ozone therapy in different areas of dentistry. An active search of articles was carried out in the databases: SciELO; PubMed and Regional Portal of the Virtual Health Library (Regional VHL), present in English or Portuguese in the periods from 2011 to 2023. However, more studies are needed on other possibilities of using this therapy within the dental field.